NADP-Dependent Isocitrate Dehydrogenase from Arabidopsis Roots Contributes in the Mechanism of Defence against the Nitro-Oxidative Stress Induced by Salinity - Marina Leterrier; Juan B. Barroso; Raquel Valderrama; José M. Palma; Francisco J. Corpas (The Scientific World Journal)
NADPH regeneration appears to be essential in the mechanism of plant defence against oxidative stress. Plants contain several NADPH-generating dehydrogenases including isocitrate dehydrogenase (NADP-ICDH), glucose-6-phosphate dehydrogenase (G6PDH), 6-phosphogluconate dehydrogenase (6PGDH), and malic enzyme (ME). In Arabidopsis seedlings grown under salinity conditions (100 mM NaCl) the analysis of physiological parameters, antioxidant enzymes (catalase and superoxide dismutase) and content of superoxide radical (O2  ∙−), nitric oxide (NO), and peroxynitrite (ONOO-) indicates a process of nitro-oxidative stress induced by NaCl. Among the analysed NADPH-generating dehydrogenases under salinity conditions, the NADP-ICDH showed the maximum activity mainly attributable to the root NADP-ICDH. Thus, these data provide new insights on the relevance of the NADP-ICDH which could be considered as a second barrier in the mechanism of response against the nitro-oxidative stress generated by salinity.